(untitled) - Onoda, Hiroo (Tokyo,New York, 1974)
Lieutenant Hiroo Onoda was officially declared dead in December 1959. At the time it was thought that he and his comrade Kinshichi Kozuka had died of wounds sustained five years earlier in a skirmish with Philippine troops. A six months search organized by the Japanese Ministry of health and Welfare in early 1959 had uncovered no trace of the two men.
Keywords: World war,World war,World War; Personal narratives, Japanese,Armistices; 1939-1945,1939-1945,1939-1945; Philippines,Lubang Island